Importance of Perceived Strategic Value of E- Commerce: The Interaction Effect of Personal Innovativeness - Malik, Muhammad Saqib; McMenemy, David (Bobcatsss, 2023)
This project explores the interaction effect of Personal Innovativeness in Information Technology (PIIT) on the relationship between determinants of Perceived Strategic Value of E-Commerce (PSVEC) and attitude towards E-Commerce adoption. Based on a survey of 15 carefully selected organisations from both the public and private sectors in Pakistan, the objectives are to (a) have an idea of what decision- makers in organisations think about the strategic value of E-Commerce in Public and Private sectors (b) examine the relationship between determinants of PSVEC and attitude towards E-Commerce adoption (c) and how PIIT impacts the relationship between determinants of PSVEC and attitude towards E-Commerce adoption. To ensure a higher degree of accuracy of results, all the variables in this study were measured on highly respected and validated scales from previous studies (Agarwal & Prasad, 1998; Subramanian & Nosek, 2001; Venkatesh & Davis, 2000). A second-generation technique; PLS Structural Equation Modelling (PLS-SEM) was used to analyse and process the data. Behavioural sciences suggest that Innovation adoption at the organisational level is more complicated than individual-level adoption as it involves both personal and organisational level factors (Rogers, 1995). E- Commerce adoption within an organisation heavily depends on the personal perceptions, beliefs and attitudes of the management (Ajzen, 1985; Davis, 1989). The study contributes to the existing knowledge by measuring and establishing relationships between personal-level factors and attitudes towards organisational level innovation adoption. An important (and unique) aspect of this study is that unlike most of the previous studies, more relevant and domain-specific latent variable PIIT is studied instead of the generic variable of personal innovativeness. As the E-Commerce adoption rate in developing economies is very low, the UN, WTO and World Bank have emphasised the developing economies to adopt E-Commerce and have initiated several programs to accelerate the E-Commerce adoption rate in underdeveloped countries. The study is likely to provide valuable insight into the nature of E- Commerce adoption in developing economies context.